Analisis Persepsi Guru Matematika dan IPA dalam Penerapan Project Penguatan Profil Pelajar Pancasila (P5) - Dini Safitri; Nurashri Partasiwi; Rika Siti Syaadah (Departement of Mathematics Education, 2024)
The development of the times, followed by the development of science and technology, has also had a big impact on the world of education. Various kinds of demands have encouraged changes in the education system, especially the curriculum. 2022 is the year when the Independent Curriculum is launched, which mandates not only the mastery of knowledge, but also the cultivation of character as outlined in the Pancasila Student Profile (P3). P3 is implemented through various co-curricular project activities, or called P5. So that P3 character strengthening can run smoothly, it is necessary to know the perception of the supervising teacher because there are still many teachers who do not have a good perception of P5 activities. The aim of this research is to determine the perceptions of teachers, especially mathematics and science teachers, regarding the implementation of P5 activities. This research uses a descriptive analysis method with a quantitative approach. The research results showed that the majority of junior high school mathematics and science teachers who were respondents had a good perception of P5 activities which included preparation, implementation, knowledge and evaluation of activities.